The Long and Short (of) Quality Ladders - KHANDELWAL, AMIT (Review of Economic Studies, 2010)
Prices are typically used as proxies for countries' export quality. I relax this strong assumption by exploiting both price and quantity information to estimate the quality of products exported to the United States. Higher quality is assigned to products with higher market shares conditional on price. The estimated qualities reveal substantial heterogeneity in product markets' scope for quality differentiation, or their “quality ladders”. I use this variation to explain the heterogeneous impact of low-wage competition on US manufacturing employment and output. Markets characterized by relatively short quality ladders are associated with larger employment and output declines resulting from low-wage competition.